Kinship of The Dayak Maanyan and Dayak Halong Languages in South of Kalimantan - Nani Darheni; Jahdiah Jahdiah; Eka Suryatin; Siti Jamzaroh (JURNAL ARBITRER, 2022)
The world’s languages do not stand alone. Every language originates from a parent language. PAN is one of the parent languages or proto-languages of the languages in the archipelago. Maanyan Dayak language or more often called Maanyan language, is the third-largest language after Banjar Malay, the Ngaju Dayak language in Kalimantan. The language enclaves of the Maanyan Dayak language spread in Central Kalimantan, South Kalimantan, Madagascar, and others. In South Kalimantan, several Dayak tribes is allegedly have a relationship with the Maanyan Dayak language. One of them is the Halong Dayak language in Balangan Regency, South Kalimantan. This study’s are aims a) find out percentages of the kinship of the two languages have ; b) describes correspondences sound both of languages; and c) describes change sounds both of them. This study uses a lexicostatistic and glottochronology approach. The results show that a) the cognates percentage in the Maanyan Dayak language and the Halong Dayak language is 69% (sublanguage); b) Separation times both of the language is 854,8 years ago; c) found some sounds correspondence is (/y/-/i/,/w/-/ ø/ /, /ŋ/-/ø /, /¥/- /y/ and /ø/-/b/ ; and the sound changes that occur include the omission of phonemes/syllables at the beginning and in the middle of words is sporadicaly ,examples sound add, substitutions, deletion sound.